Alternatives to Increase Body Immunity Against the Danger of the Covid 19 Virus Outbreak for Education Student Elementary School Teacher at Universitas Muslim Nusantara Al-Washliyah Medan - Muhammad Noer Fadlan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
In this study, the researcher has the aim of providing information regarding alternatives and effective ways to avoid the covid 19 virus by exercising, this information is done by visiting several sites to collect data that is considered relevant, in this study it can be concluded that it is so important about the role of exercise in maintaining the immune system to stay healthy in daily activities. Then furthermore, this also aims to provide information for student participants in the primary school teacher education study program so that they can be more careful in their activities and understand how to exercise in a pandemic situation where the COVID-19 virus is not visible masks and adhere to health protocols